2021
DOI: 10.1093/cid/ciab975
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Coronavirus Disease 2019 (COVID-19) Vaccine Hesitancy Among People Who Inject Drugs in the San Diego-Tijuana Border Region

Abstract: Background People who inject drugs (PWID) are vulnerable to acquiring SARS-CoV-2. We examined correlates of COVID-19 vaccine hesitancy among PWID in the U.S.-Mexico border region, of whom only 7.6% had received ≥one COVID-19 vaccine dose by September, 2021. Methods Between October, 2020 and September, 2021, participants aged ≥18 years from San Diego, California, USA and Tijuana, Baja California, Mexico who injected drugs within the last month completed surveys and SARS-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 26 publications
3
47
0
Order By: Relevance
“…Nonetheless, these data are reassuring, particularly because data from other substance-using cohorts have suggested low levels of intention to be vaccinated. 10,12 In sum, our findings suggest that efforts to vaccinate all adults in Maryland were generally effective for the PWID population.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Nonetheless, these data are reassuring, particularly because data from other substance-using cohorts have suggested low levels of intention to be vaccinated. 10,12 In sum, our findings suggest that efforts to vaccinate all adults in Maryland were generally effective for the PWID population.…”
Section: Discussionmentioning
confidence: 65%
“… 10 , 11 Approximately one-third of PWID in San Diego, California, and Tijuana, Mexico, were hesitant to receive the vaccine, with most endorsing ≥1 COVID-19–related conspiracy theory. 12 Despite the high prevalence of comorbidities and elevated risk for severe illness and death from COVID-19 among PWID, to our knowledge, no studies have investigated attitudes about vaccination and vaccine uptake in this population after vaccines became widely available in the United States.…”
mentioning
confidence: 99%
“…Vaccine hesitancy in this study (48%) was comparable to that observed in our aforementioned study of 100 people who inject drugs in Melbourne prior to the publication of studies on vaccine efficacy and the start of the vaccine rollout. However, it is higher than a study of people who inject drugs in San Diego, USA, which reported that one‐third of participants were vaccine hesitant [ 13 ]. This difference may be a result of the different pandemic experiences in the two countries; the USA has seen far greater COVID‐19‐related morbidity and mortality than Australia, and vaccine hesitancy is linked to perceived low risk of disease acquisition [ 14 ].…”
Section: An Update On Vaccine Intentions Since Vaccine Rollout Commen...mentioning
confidence: 87%
“…An earlier study conducted by our binational team found that only 7.6% of PWID living on either side of the San Diego-Tijuana border reported having had at least one COVID-19 vaccine dose by September 2021, and nearly one-third reported being vaccine hesitant ( 17 ). There was no difference in COVID-19 vaccine hesitancy between PWID residing in San Diego vs. Tijuana or by race/ethnicity but younger PWID and those who endorsed COVID-19 disinformation were more vaccine hesitant ( 17 ). Disinformation has been described as the deliberate spread of false information, as opposed to misinformation, which is spread without malicious intent ( 2 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…By June 25, 2021, Baja California reported being close to becoming the first state in Mexico to achieve full vaccination for most of its adult residents ( 15 , 16 ) following a donation of J&J/Janssen vaccine from the United States; however, vaccine uptake was lower in some marginalized populations ( 17 ). As in other Mexican cities, individuals in Tijuana seeking COVID-19 vaccination were required to register online and enter their CURP ( Clave Única de Registro de Población ; Mexican official unique identifier) to obtain an appointment and were asked to print the appointment card or present their CURP to verify their identity ( 18 ), which has been shown to be a barrier to health services in other settings ( 19 ).…”
Section: Introductionmentioning
confidence: 99%